2022
DOI: 10.1155/2022/3044371
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Fear of COVID-19 and Self-Medication and the Rate of Antibiotic Use in Patients Referred to COVID-19

Abstract: Introduction. The coronavirus pandemic can cause anxiety and stress among people, which can make them practice self-medication. This study aimed to investigate the relationship between fear of corona and self-medication and antibiotics use. Methods. In a convenience sampling method, 250 people referring to COVID-19 centers including 16-hour comprehensive health services in Kermanshah, Iran, who tested positive and were not hospitalized were extracted from the SIB system. Data collection tools include three que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The Prevention factor (F4) is an anticipatory behavior in relation to undesirable symptoms or the threat of a condition. This supports other findings indicating a relationship between self-medication and fear of illness during the COVID-19 pandemic (Faraji et al, 2022 ). Furthermore, some individuals may view self-medication, including vitamins and supplements, as a proactive way to stay healthy, preventing potential health problems (Santos and Barros Filho, 2002 ; Lawand et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…The Prevention factor (F4) is an anticipatory behavior in relation to undesirable symptoms or the threat of a condition. This supports other findings indicating a relationship between self-medication and fear of illness during the COVID-19 pandemic (Faraji et al, 2022 ). Furthermore, some individuals may view self-medication, including vitamins and supplements, as a proactive way to stay healthy, preventing potential health problems (Santos and Barros Filho, 2002 ; Lawand et al, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…The COVID-19 pandemic has exacerbated this trend, influenced by several factors. Fear of catching the virus has made people reluctant to seek medical care at clinics or hospitals [7]. Furthermore, lockdowns and restrictions have hindered access to healthcare services, leading to an increase in self-medication [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as COVID-19 studies have recently reported, fear of illness and health anxiety can lead to incorrect medication behaviors, including self-medication and antibiotics overuse [ 11 , 12 ], probably due to an overestimation of an efficacy in unnecessary conditions [ 13 ]. Indeed, widespread lack of knowledge concerning antibiotics and their associated risks contributes to incorrect antibiotic intake [ 14 ], aligning with the low knowledge and awareness reported in the World Health Organization’s 2015 survey across 12 countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%